Analysis of amplang processing business UD. Taufik Jaya Makmur in Sidomulyo Village Samarinda Ilir Sub-District, Samarinda City - Novianti, Rina; Helminuddin , Helminuddin; Fahrizal, Wahyu (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
This study aims to determine the cost and profit of amplang processing business and determine the feasibility of amplang processing business. This research uses saturated sampling method or census. Data analysis using cost analysis and business feasibility analysis. Based on the results of the analysis of costs incurred amounted to Rp 100.696.857 / month, profit of Rp 139.303.143 / month, R / C value of 2.38, payback period 1.16 month.